BS3 Novel strategy using hesc-derived cardiomyocytes to explore the critical importance of the apelin receptor in the cardiovascular system. (4th June 2021) - Macrae, Robyn; Colzani, Maria; Robinson, Emma; Bayraktar, Semih; Williams, Thomas; Kuc, Rhoda; Maguire, Janet; Sinha, Sanjay; Davenport, Anthony
Abstract : Introduction: Apelin receptor activation promotes beneficial vasodilation and positive inotropy 1 and is critical for early cardiac development. 2 In cardiovascular disease states, including heart failure, expression of apelin receptor endogenous peptide ligands, apelin and Elabela, are downregulated. 1 We aim to use human embryonic stem cell (hESC)-derived cardiomyocytes (hESC-CMs) as a model to interrogate the role of the apelin receptor in the cardiovascular system and the potential of targeting the receptor therapeutically. Here, we have generated a system to inducibly knockdown the apelin receptor in hESC-CMs to examine the effects on differentiation of hESC to cardiomyocyte, and the effects on function of the resulting hESC-CMs. Methods: A short hairpin RNA based apelin receptor (shAPLNR) inducible knockdown system was generated in pluripotent hESCs, utilising the sOPTiKD system as described previously, 3 before differentiating to hESC-CMs. Inclusion of tetracycline in the culture medium was used to induce knockdown, with knockdown efficiency determined by qRT-PCR and radioligand binding. RNA-sequencing analysis and a panel of phenotypic assays were performed to examine effects of apelin receptor knockdown on cardiomyocyte differentiation and function. Results: We have previously demonstrated that hESC-derived cardiomyocytes express the apelinergic system at a similar level to adult cardiomyocytes (Bmax hESC-CMs 21 fmol/mg versus adult 14 fmol/mg). Apelin receptor expression was significantly reduced in hESCs and hESC-CMs by tetracycline inclusion at both RNA and protein level (84.2% ± 4.3 and 82.8% ± 3.9 compared to control in hESCs and hESC-CMs, respectively). Interestingly, efficiency of differentiation to cardiomyocyte was reduced compared to control cells (77.8% ± 5.5 cardiomyocyte control vs 22.2% ± 7.4 cardiomyocyte knockdown). RNA-sequencing analysis revealed 272 differentially expressed genes involved in pathways related to electrophysiological signalling, adhesion and the cytoskeleton. Discussion: We have successfully shown knockdown of apelin receptor expression in hESC-CMs. To our knowledge, this is the first use of this system to knockdown expression of a GPCR. This system allows detailed characterisation of apelin receptor activation in cardiovascular development and disease pathogenesis, providing an innovative approach to develop strategies to target the apelin receptor therapeutically in cardiovascular disease, where novel treatments are urgently needed. Conflict of Interest: None References: Yang et al. Circulation 2017;135 :1160–1173. Chng et al. Developmental Cell 2013;27 (6):672–680. Bertero et al. Development 2016;143 :4405–4418.